2004
DOI: 10.1182/blood-2003-02-0524
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient expression of transgenic proteins by naked DNA-transfected dendritic cells through terminal differentiation

Abstract: Dendritic cells (DCs) play a key role in the induction and control of immunity. Genetic engineering of DCs is a promising approach for the development of a broad range of immunomodulatory strategies, for purposes ranging from genetic immunization to tolerance induction. The development of DC-based immunotherapies is limited by the inability to efficiently transfect DCs using naked DNA. Here we demonstrate that after plasmid DNA delivery, the transgene expression level controlled by the human immediate-early cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 46 publications
0
33
0
Order By: Relevance
“…We have recently shown that nonviral transfection of DCs can be achieved using naked DNA with very high transfection efficiencies (46). Although the use of plasmid DNA to transfect DCs results in nonintegrating transfection, we demonstrated more sustained expression of H-2K b -SIINFEKL complexes on the surface of transfected DCs compared with DCs pulsed with SIINFEKL.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…We have recently shown that nonviral transfection of DCs can be achieved using naked DNA with very high transfection efficiencies (46). Although the use of plasmid DNA to transfect DCs results in nonintegrating transfection, we demonstrated more sustained expression of H-2K b -SIINFEKL complexes on the surface of transfected DCs compared with DCs pulsed with SIINFEKL.…”
Section: Discussionmentioning
confidence: 56%
“…This may be a critical issue for immunotherapy, particularly in the setting of tumor-bearing hosts or victims of viral infections such as HIV, in whom immunizations will need to overcome pre-existing immunosuppressive mechanisms. We recently demonstrated, by direct comparison, that DCs expressing transgenic Ag after nonviral transfection induced more potent T cell immunity than peptide/ protein-pulsed DCs (46). As yet there are no reports comparing the immunogenicity of lvv-transduced DCs with that of peptide/protein-pulsed DCs.…”
Section: Endritic Cells (Dcs)mentioning
confidence: 99%
See 1 more Smart Citation
“…In general, DCs generated from adherent celldepleted PB monocytes are used for the development of gene-modified DC vaccines that express known tumor antigens, using either non-viral or viral vectors. 7,9,10,[31][32][33] We, and others, have shown the potential of HIV-1-based lentiviral vectors in delivering transgene to human monocyte-derived DCs and the induction of T-cell responses. 25,[34][35][36] The initial aim of the current study was to develop and optimize a clinically feasible method to generate gene-modified DC vaccines using an SIN lentiviral vector for cancer immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The enhanced transgene expression detected in DCs following stimulation with TNF-a Immune responses to gene-modified dendritic cells N Chinnasamy et al and sCD40L correlated with their terminal differentiation as assessed by further upregulation of costimulatory molecules (CD80, CD86, CD40, and CD54) and MHC molecules, and also by expression of maturation marker CD83 (data not shown) as suggested previously. 31 Similarly, increased expression of eGFP in transduced lymphocytes contaminants after exposure to TNF-a and sCD40L might be due to changes in their activation status, probably by receiving costimulatory and immunostimulatory factors from mature DCs due to the direct effect of TNF-a and sCD40L.…”
Section: Lentivirus Transduction Of Monocyte-derived Dcsmentioning
confidence: 99%